2021
DOI: 10.3390/agronomy11081587
|View full text |Cite
|
Sign up to set email alerts
|

Licorice, Doum, and Banana Peel Extracts Inhibit Aspergillus flavus Growth and Suppress Metabolic Pathway of Aflatoxin B1 Production

Abstract: Three different concentrations of four (ethanol, acetone, methanol, and diethyl ether) extracts of licorice, doum, and banana peel were evaluated for antifungal and antimycotoxigenic efficiency against a maize aflatoxigenic fungus, Aspergillus flavus. Among them, the licorice diethyl ether 75% extract was intensely active, showing the best wet and dry weight inhibition and exhibiting the highest efficacy ratio (91%). Regarding aflatoxin B1 (AFB1) production, all the plant extracts tested were effective against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 80 publications
4
10
0
Order By: Relevance
“…They reported similar reductions in Aspergillus fungal dry weight after using essential oils. Doum, banana, and licorice peel extracts exhibited similar decreases [15]. The findings were similarly consistent with those of Yazdani et al [68] and Oliveira and Furlong [29].…”
Section: Afb1 Productionsupporting
confidence: 91%
See 3 more Smart Citations
“…They reported similar reductions in Aspergillus fungal dry weight after using essential oils. Doum, banana, and licorice peel extracts exhibited similar decreases [15]. The findings were similarly consistent with those of Yazdani et al [68] and Oliveira and Furlong [29].…”
Section: Afb1 Productionsupporting
confidence: 91%
“…Generally, the aflR and aflS are essential regulatory genes for AFB1 synthesis. Many reports assed significant correlations between the transcriptional levels of the two regulatory genes and AFB1 production [15,80]. The results showed the downregulation of two genes, aflR, and aflS, for all treatments compared to infected (untreated) controls.…”
Section: Total Phenolics Content Of the Fruit Peel Extractsmentioning
confidence: 87%
See 2 more Smart Citations
“…This variation in mycotoxin behavior as a response to different shaking speeds could be associated with the differences in their molecule's chemical and physical properties and molecular weights (Omar, 2016). This notice matched those of (Youssef, 2019a) et al, 2015) and (Youssef, Qari, Behiry, et al, 2021;Youssef, Qari, Matar, et al, 2021) showed mycotoxins like aflatoxin and Zear can be significantly inhibited by plant derivatives such DOU, GTL, banana peels, and LIC.…”
Section: Shacking Processsupporting
confidence: 59%